Refleksi Praktik Mengajar Bahasa Inggris Di Sekolah Dasar Negeri - Vanisha Putri Dwiyanti; Saputra, Erwin Rahayu (Universitas Islam Ahmad dahlan, 2024)
Elementary School Teacher Education students as prospective elementary school teachers have an important role in developing and improving the quality of education in Indonesia. Therefore, students need to get adequate provision. One way to get this provision is by doing teaching practice in elementary school. Teaching practice provides many lessons for students, both positive and negative, which can be used as evaluation material. One effective way of evaluation is reflection. Through reflection, students can assess and measure the process and results of learning, know the strengths and weaknesses, and plan improvements for further learning. This study aims to determine the results of student reflection after implementing English language learning in elementary schools. This research used descriptive qualitative approach with narrative inquiry method. The results of the research that have been obtained are students present a detailed reflection report after taking action.